A new genus of Lysitermini (Hymenoptera: Braconidae: Lysiterminae) from Madagascar and its taxonomic placement based on 28S rDNA sequence data - Belokobylskij, Sergey A.; Zaldivar-Riverón, Alejandro; León-Regagnon, Virginia; Quicke, Donald L.j. (Zootaxa, 2007)
A new genus and species of Lysitermini, Atritermus pedestris Belokobylskij, Zaldivar-Riverón & Quicke, are described from Madagascar. The taxonomic placement of the new genus within Lysiterminae is discussed based on a phylogenetic analysis using 28S rDNA gene sequences. A key to world genera of Lysitermini is provided.Un nuevo género y especie de Lysitermini, Atritermus pedestris Belokobylskij, Zaldivar-Riverón & Quicke, son descritos para Madagascar. La ubicación taxonómica del nuevo género dentro de Lysiterminae es discutida con base en un análisis filogenético usando secuencias del gen ribosomal 28S. Se presenta una clave para los géneros de Lysitermini del mundo.